Treatment and Valorisation of Saline Wastewater Principles and Practice - Val del Río, Ángeles (IWA Publishing, 2021)
This book covers the principles and practices of processes and technologies applied for the treatment of saline wastewater with discharge and reuse purpose, and those applied for its valorisation. Saline wastewater was considered to present electrical conductivities over 2 mS/cm, which is the limit for crop irrigation. Saline wastewater management is described with respect to: Basics about salinity characterisation and environmental impact Effects of salinity on the wastewater physical-chemical treatments Effects of salinity on biological treatment processes Valorisation of saline wastewater for energy and materials production Technologies for saline wastewater treatment and salt recovery Urban and industrial saline wastewater treatment Treatment and Valorisation of Saline Wastewater includes two case studies evaluating the treatment of the effluents from a fish cannery and from a WWTP with seawater intrusions in the collecting system. This book is intended as a text reference book for post-graduate, PhD students and researchers interested in the effects of salinity on the wastewater treatment and valorisation processes. It also serves as a reference text for professionals working in the industrial and urban wastewater sector that deal with saline wastewater.